2020
DOI: 10.2174/1874210602014010329
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Dental Interns and Dentists on Implants and Implant-Retained Restorations in Jeddah, Saudi Arabia

Abstract: Objectives: This cross-sectional study aimed to assess the knowledge and attitudes of dental interns and dentists in Jeddah, Saudi Arabia, about Cement-Retained Restoration (CRR), Screw Retained Restoration (SRR), and implant restoration. Methods: A total of 530 dentists and students participated in the study. Data were collected using a self-administrated questionnaire modified from previous studies. The collected da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
1
Order By: Relevance
“…On the other hand, more than half of the participants in this study (65.3% of graduates of some Saudi dental schools and 41.3% of some non-Saudi dental schools) also reported that case selection is the most significant standard for the success of dental implants procedure which is lower than those participants revealed in a previous Saudi study [37].…”
Section: Discussioncontrasting
confidence: 80%
“…On the other hand, more than half of the participants in this study (65.3% of graduates of some Saudi dental schools and 41.3% of some non-Saudi dental schools) also reported that case selection is the most significant standard for the success of dental implants procedure which is lower than those participants revealed in a previous Saudi study [37].…”
Section: Discussioncontrasting
confidence: 80%
“…This can be due to the complex nature of these procedures and very few senior practitioners were included in the study. Another study by Al-Dajani et al shows that sinus lift surgeries for implants required additional skills from the implant practitioner [ 22 ].…”
Section: Discussionmentioning
confidence: 99%